The First Celebration of Freedom, “Nowruz” - Umarov Mamur Botashikovich (International Journal on Integrated Education, 2022)
The article deals with the first holiday Nowruz celebrated on the eve of independence and its role in the restoration of national values, as well as the basis of recognition of holidays in Uzbekistan - "theatrical, musical, choreographic composition".